PENGARUH PERSPEKTIF DAN JENIS UKURAN DALAM BALANCED SCORECARD TERHADAP EVALUASI KINERJA - Hariman Bone; Mahfud Sholihin (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya(STIESIA) Surabaya, 2012)
This study aims to investigate whether an evaluator has propensity to more weigh common financial measurement than unique financial measurement and common nonfinancial measurement when evaluating performance. We conduct two experiments where participants act as senior management to evaluate two divisions. The first experiment examines the existence of propensity of managers to more weigh common financial measurement than unique financial measurement. The ANOVA repeated measurement show that participants more weigh common financial measurement than unique financial measurement. The second experiment examines the existence of propensity of participants to weigh common financial measurement than common nonfinancial measurement. The result shows that participants more weigh common financial measurement than common nonfinancial measurement in their performance evaluation.